Սպանիա եւ Մեծ Եղեռնը (1915-1923) - Մատթէոսեան, Վարդան (տպ. Atlas)
The Spanish press reported on the Armenian Genocide as it happened, while the government was also kept informed through reports by Ambassador Julian Maria del Arroyo, stationed in Constantinople. Spain’s strict neutrality throughout World War I allowed King Alfonso XIII to pursue a policy of humanitarian assistance to all sides without distinction, which was met with unreserved praise by the press of both warring sides. Armenians also addressed the Spanish king through various channels, and on several occasions the monarch directed his representatives to make efforts to assist Armenian intellectuals, even in cases when those efforts proved futile. Appeals to Alfonso XIII were made from 1915 to the end of the war, as revealed by documents in Spanish and Ottoman archives, as well as evidence in the Armenian press. After the war, Spain became a non-permanent member of the Council of the Society of Nations. In April-May 1920 it was speculated that it could take over the mandate of Armenia. Along with U.S. President Woodrow Wilson and Brazil, Spain offered its mediation in late 1920, following the outcome of the Armenian-Turkish war. Arroyo’s successor, Ambassador Juan Servert у Vest, was also approached to ask for Spanish help in an aborted plan to transport Armenian migrants to South America following the catastrophe of Smyrna in September 1922. Spain also made a financial contribution to help Armenian and Greek refugees reeling from the catastrophe. This study provides an overview of Spanish actions in the period 1915-1923 through an investigation of published documents and information from the Armenian and Spanish press.
Keywords: Պատմութիւն